(2(y-3))/3=-3y

Simple and best practice solution for (2(y-3))/3=-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2(y-3))/3=-3y equation:


y in (-oo:+oo)

(2*(y-3))/3 = -3*y // + -3*y

(2*(y-3))/3-(-3*y) = 0

(2*(y-3))/3+3*y = 0

(2*(y-3))/3+(3*3*y)/3 = 0

2*(y-3)+3*3*y = 0

11*y-6 = 0

(11*y-6)/3 = 0

(11*y-6)/3 = 0 // * 3

11*y-6 = 0

11*y-6 = 0 // + 6

11*y = 6 // : 11

y = 6/11

y = 6/11

See similar equations:

| (4x+16)/(8)=2x-1 | | -3-11=9x+15-8x | | (4(y-5))/3=-4y | | -x-7y=-18 | | 2-5i=-x+10yi | | -9x+5+10x=-11+13 | | n-12=24 | | (7/2)+(5/2y)=2y-3 | | y=3(3)-9 | | 176-4x=23x+17 | | 0.17-0.01(x+2)=0.03(3-x) | | 9(x+1)-1=3x+6(1+x) | | 5c-7c=(-32) | | 8+3x=24+14 | | 18a-45b-9c= | | A-x=3a | | (x/4)-1=(x/9)+4 | | 4(x-5)=2x+25 | | 4x-3(3x-9)=12 | | y/4+y=10 | | g+10/3=10 | | 5c(3c+2d)-2c(c-d)= | | y^2+5y+6y^0=0 | | ((4x+5)(6)(2x+5)^2+(-8)(2x+5)^3)/(4x+5)^3 | | 81t=-8.1 | | 4p+28q+12r= | | 175 x 104 = | | -7x+9=7x-47 | | 3/7+k/8=5/56 | | 0.36=18 | | 6x+1=6(x-2) | | 12x^2-6=0 |

Equations solver categories